Herpes Simplex virus type 2 myeloradiculitis with a pure motor presentation in a liver transplant recipient. Issue 1 (1st January 2020) - Abati, Elena; Gagliardi, Delia; Velardo, Daniele; Meneri, Megi; Conte, Giorgio; Cinnante, Claudia; Bresolin, Nereo; Comi, Giacomo; Corti, Stefania
Abstract: In this case report, we describe the first PCR‐confirmed case of HSV2 myeloradiculitis with a purely motor presentation, occurring in a 68‐year‐old liver transplant recipient. The patient reported ascending weakness with no sensory nor sphincteric symptoms, thereby resembling acute demyelinating inflammatory neuropathy, or Guillain‐Barré syndrome. HSV2 was detected in cerebrospinal fluid by PCR, and the patient was successfully treated with intravenous Acyclovir.